Bahasa Inggris - Lutviah, Lutviah (Universitas 17 Agustus 1945 Surabaya, 2025)
This study investigates Kompas’ media framing of celebrity participation in the “Emergency Warning” movement in Indonesia. It employed a qualitative research approach using Entman’s four functions of framing: problem definition, causal interpretation, moral evaluation, and treatment recommendation (Entman, 1993).The analysis reveals that Kompas constructed a predominantly positive narrative around celebrities involved in the movement. Supportive celebrities were not only portrayed as entertainers, but also as moral agents and catalysts for civic action who are committed to defending democratic values. Meanwhile, those who remained neutral or silent were portrayed more critically. Such binary framing suggests that Kompas actively constructed a moral framework around the movement that guides audiences to view celebrity support as virtuous and disengagement as morally unacceptable. Additionally, selective emphasis on celebrities over other key opinion leaders suggests a strategic use of celebrity popularity to legitimize the movement and broaden its public appeal. This study concludes that Kompas used celebrity participation to justify the movement’s legitimacy, mobilize public sentiment, and contribute to the movement’s overall visibility and resonance. These findings highlight the influential role of media framing in shaping public discourse and civic action, particularly through the strategic deployment of celebrity voices.